Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India - Tamang, Lakpa; Sinha, Bikramjit (Zootaxa, 2016)
Physoschistura walongensis, new species, is described from the bank of the Lohit River (upper Brahmaputra River basin) in the eastern most part of the state Arunachal Pradesh at an altitude of 1096 m above sea level. The new species is distinguished from its congeners by the following combination of characters: an incomplete lateral line extending at least to the anal-fin origin and maximally to the tip of the adpressed anal fin, with 71–89 canal pores; a rounded suborbital flap, the posterior margin of which slightly exceeds the anterior orbital margin, occupying less orbital area; body with 11–18 irregular vertical bars on the flank, bars more irregular on the anterior portion of the body than on posterior; 1–4 bars bifurcate ventrally; 1–4 saddles along the ventrolateral side of the body; a moderately thick W-shaped basicaudal bar; a prominent axillary pelvic fin lobe; dark brown mottled markings on the head; and forked caudal fin with 9 upper + 8 lower branched rays.